Correlates of protection against SARS-CoV-2 in rhesus macaques - McMahan, Katherine; Yu, Jingyou; Mercado, Noe B.; Loos, Carolin; Tostanoski, Lisa H.; Chandrashekar, Abishek; Liu, Jinyan; Peter, Lauren; Atyeo, Caroline; Zhu, Alex; Bondzie, Esther A.; Dagotto, Gabriel; et al. (Nature (London), 2021)
Recent studies have reported the protective efficacy of both natural 1 and vaccine-induced 2 – 7 immunity against challenge with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in rhesus macaques. However, the importance of humoral and cellular immunity for protection against infection with SARS-CoV-2 remains to be determined. Here we show that the adoptive transfer of purified IgG from convalescent rhesus macaques ( Macaca mulatta ) protects naive recipient macaques against challenge with SARS-CoV-2 in a dose-dependent fashion. Depletion of CD8 + T cells in convalescent macaques partially abrogated the protective efficacy of natural immunity against rechallenge with SARS-CoV-2, which suggests a role for cellular immunity in the context of waning or subprotective antibody titres. These data demonstrate that relatively low antibody titres are sufficient for protection against SARS-CoV-2 in rhesus macaques, and that cellular immune responses may contribute to protection if antibody responses are suboptimal. We also show that higher antibody titres are required for treatment of SARS-CoV-2 infection in macaques. These findings have implications for the development of SARS-CoV-2 vaccines and immune-based therapeutic agents. Adoptive transfer of purified IgG from convalescent macaques protects naive macaques against SARS-CoV-2 infection, and cellular immune responses contribute to protection against rechallenge with SARS-CoV-2.